Probiotic-Inspired Nanomedicine Restores Intestinal Homeostasis in Colitis by Regulating Redox Balance, Immune Responses, and the Gut Microbiome - Xu, Jiaqi (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2022 Wiley-VCH GmbH.